Climate Variability Masked Greening Effects on Water Yield in the Yangtze River Basin During 2001–2018. Issue 1 (4th January 2022) - Zhang, Jiehao; Zhang, Yulong; Sun, Ge; Song, Conghe; Li, Jiangfeng; Hao, Lu; Liu, Ning
Abstract: Rapid global vegetation greening has been observed for the past two decades, but its implications to the hydrological cycle are not well understood in many regions, including the Yangtze River Basin (YRB). This study used a remote sensing‐driven ecosystem model, the Coupled Carbon and Water model, to fully examine the individual and combined hydrological effects of vegetation and climate changes through a series of modeling experiments. During the study period (2001–2018), the vegetation showed a significant greening trend with the mean annual normalized difference vegetation index increasing at a rate of 0.4% per year ( p  < 0.001). In contrast, climate exhibited a marginal wetting trend with annual precipitation increasing at a rate of 6.7 mm/yr ( p  = 0.08). Annual evapotranspiration (ET) in the YRB significantly increased (3.1 mm/yr, p  = 0.01) primarily due to enhanced ecosystem productivity associated with vegetation greening, rather than climatic factors. However, the enhancement in ET did not lead to a significant decline in total water yield at the YRB scale. The large inter‐annual variability of precipitation masked the effects of vegetation greening on water yield. Overall, our study indicated that the recent land "greening up" has accelerated the regional hydrological cycle through increasing ET and resulted in enhanced risks of water resource shortage. Our findings highlighted the close connection between land cover dynamics and hydrological cycle under climate variability in one of the world's largest river systems. Effective basin water resource management must consider hydrological response to vegetation greening and climate change. Key Points: The Yangtze River basin experienced significant vegetation greening during 2001–2018 The recent vegetation greening led to a significant increase in evapotranspiration (ET) Precipitation variability masked the effects of ET increase on water yield